Total Phenolic Content of Natural Deep Eutectic Solvent (NADES) Extraction in Comfrey (Symphytum officinale) - Andiri Niza Syarifah; Herman Suryadi; Abdul Mun'im (Universitas Aisyah Pringsewu, 2022)
Objective: The most common type of phytochemical is phenolic compounds. These compounds are mostly found in the plant kingdom, and extraction is one of the first and most important stages before any use. The green chemistry trend has encouraged the researcher to discover and generate innovative solvents in the extraction of phenolic compound (PC) as a strategy to toxic and potentially hazardous organic solvents. Natural Deep Eutectic Solvents (NADES) have recently been used as phenolic compound extraction solvents. The objective of this study is to determine the total phenolic contents of the NADES extract from comfrey (Symphytum officinale). Methods: This study used choline chloride-urea, choline chloride-glycerol and choline chloride-sucrose combination of NADES for extraction of phenolic compound in comfrey. The extraction was helped using Ultrasound Assisted Extraction (UAE). The extracted material was examined using a UV-Vis spectrophotometer. Results: The results showed that the total phenol of choline chloride-urea, chloride-glycerol and choline chloride-sucrose NADES comfrey extraction was 2.069, 1.566, and 1.906 mg GAE /gram of dry powder, respectively. Conclusion: Based on the result, it can be concluded type of NADES combination showed a different level of phenolic extraction. The best phenolic extraction was shown in the combination of choline chloride-urea. Abstrak: Latar belakang: Fenol adalah senyawa kimia yang paling umum ditemukan dalam tanaman. Proses ekstraksi berperan penting dalam pemisahan senyawa fenol dari tanaman sebelum dimanfaatkan. Saat ini penelitian banyak difokuskan pada proses ekstraksi yang ramah lingkungan. Salah satunya adalah menggunakan Natural Deep Eutectic Solvent (NADES) dalam proses ekstraksi senyawa fenol. Tujuan penelitian ini adalah menghitung kadar fenol total dalam ekstrak NADES tanaman komfrey. Metode: Penelitian ini menggunakan NADES yang berasal dari kolin klorida-gliserol, kolin klorida-urea dan kolin klorida-sukrosa. Proses ekstraksi menggunakan Ultrasound Assisted Extraction (UAE) untuk mempercepat proses ekstraksi. Penentuan kadar fenol total diukur menggunakan spectrophotometer UV-Vis. Hasil: Kadar fenol total dalam ekstrak NADES masing-masing adalah 1.566, 2.069 and 1.906 mg GAE /gram sampel. Kesimpulan: Berdasarkan hasil yang diperoleh dapat disimpulkan bahwa kombinasi masing-masing NADES memberikan kemampuan ekstraksi senyawa fenol yang berbeda-beda. Kadar fenol total terbaik dihasilkan oleh kombinasi NADES kolin klorida-urea.